(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Harvesting is one of the major labor intensive works in rice cultivation. Appropriate harvesting machinery is urgently needed to reduce labor and production costs. Production cost of rice becomes high due to labor shortage and high wage rate during harvesting time. Techno-economic performance of Korean self-propelled reaper (KR), China self-propelled reaper (CR) and BRRI reaper (BR) were evaluated in order to identify the field constrains and problems of the reapers at Mithapukur of Rangpur, Bangladesh during Aman season of 2013. The actual field capacities of the KR, CR and BR were found 0.18, 0.17 and 0.15 ha h–1with the corresponding field efficiency of 55, 68 and 56%, respectively. The variation of field capacity among the models was due to turning time losses, weight of the reaper and operator’s skill. The fuel consumption of the reapers was 4.11, 2.61 and 8.39 l ha–1 for KR, CR and BR, respectively. The shattering loss of paddy harvesting was 1.66, 1.50 and 1.45% for KR, CR and BR, respectively. The break-even area of the reapers was 9.15, 7.82 and 8.43 ha yr-1 for KR, CR and BR, respectively. It is evident that the reaper could be used successfully as labor saving and user friendly technology to eliminate post-harvest problems in Bangladesh. J. Bangladesh Agril. Univ. 16(1): 144-150, April 2018